Konsep Tarbiyah, Ta’lim Dan Ta’dib Dalam Al-Qur’an - Muhammad Ridwan (Nazhruna: Jurnal Pendidikan Islam, 2018)
This research is motivated by various conceptions about education in Islam is apparently has the uniqueness of the meaning contained in Al-Qur'an and Al-Hadith, because it shows the richness of the meaning of the words in the verses and every sentence. Educational concepts or theories experience a heated debate for experts or scientists. Actually, many terms are considered to be close to the meaning of education, among them: Al-Tarbiyah, At-Ta’lim, At-Ta’dib atau al Adab, At-Tahzib, Al- Wa’adz atau Mau’idzah, Ar-Riyadhah, At-Tazkiyyah, Al-Talqin, At-Tadris, At-Tafaqquh, At-Tabyin, At-Tazkiroh, and others. Why is the term tarbiyah used? Is the term tarbiyah indeed able to describe precisely the basic concepts and principles of Islamic education that from of the teachings of Islam? The purpose of this study is to explain and analyze the comparison between the concept of Tarbiyah, Ta'lim and Ta'dib. The research method used is literature research and qualitative descriptive analysis with philosophical approach. The result of the research is that the language is from the same root of the form tsulasi mujarrod with wazan madda-yamuddu, there are rabba-yarubbu, ‘allama-yu’allimu and addaba-yuaddibu and the terms concept of the term tarbiyah, ta'lim and ta'dib have some sense but the tigands are emplicitly related to each other.